Surface characterizations of membranes and electrospun chitosan derivatives by optical speckle analysis. (6th December 2019) - Rizwan, Muhammad; Ganjkhani, Yasaman; Farzam Rad, Vahideh; Bazzar, Maasoomeh; Yar, Muhammad; Yahya, Rosiyah; Moradi, Ali‐Reza
Abstract : In this paper, we show that laser speckle pattern provides useful information toward revealing discrimination between nanofibers and membranes. Chitosan materials particularly organosoluble chitosan derivatives have a number of applications. The surface characteristics of these materials are very critical for specific applications. The analysis of laser speckles, both numerical and graphical, includes information about the surface structure. The development of digital electronics brought the ease of image processing and has opened new perspectives for a spectrum of laser speckle analysis (LASCA) applications. Our results show reasonable differences between the LASCA parameters of nanofibers and membranes. The methodology may be considered as a quantitative assessment tool for similar samples.